The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/hmg/ddx208
|View full text |Cite
|
Sign up to set email alerts
|

Dental pulp stem cells for the study of neurogenetic disorders

Abstract: Dental pulp stem cells (DPSC) are a relatively new alternative stem cell source for the study of neurogenetic disorders. DPSC can be obtained non-invasively and collected from long-distances remaining viable during transportation. These highly proliferative cells express stem cell markers and retain the ability to differentiate down multiple cell lineages including chondrocytes, adipocytes, osteoblasts, and multiple neuronal cell types. The neural crest origin of DPSC makes them a useful source of primary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Inhibition of glutamate release has also been used previously as a validated cell assay for measuring the potential activity of Arg0 on the inhibition of neuronal exocytosis 29 . Primary human dental pulp stem cells derived neurons (DPSC neurons) were chosen due to its ability to differentiate into functionally active neurons and reduced problems associated with epigenetic changes and re-programming, as compared to induced pluripotent stem cells 30 . Comparing to the undifferentiated dental pulp stem cells (DPSC), a significantly higher fluorometric readout (indicative of the amount of glutamate released) was observed in the neuronally differentiated DPSC neuron group, as compared to blank and DPSC group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of glutamate release has also been used previously as a validated cell assay for measuring the potential activity of Arg0 on the inhibition of neuronal exocytosis 29 . Primary human dental pulp stem cells derived neurons (DPSC neurons) were chosen due to its ability to differentiate into functionally active neurons and reduced problems associated with epigenetic changes and re-programming, as compared to induced pluripotent stem cells 30 . Comparing to the undifferentiated dental pulp stem cells (DPSC), a significantly higher fluorometric readout (indicative of the amount of glutamate released) was observed in the neuronally differentiated DPSC neuron group, as compared to blank and DPSC group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with nanofiber fabrication, primary neurospheres are obtained from DPSCs isolated from human dental pulp as schematized in Figure a. Intended to allow our study to start from a unique and well‐defined cell population that is then cultured on different classes of scaffolds, the intermediate neurosphere generation is associated with the induction of neuronal precommitment in the used cells . This will lead to remarkable results upon growth on some of the investigated scaffolds, as detailed in the following.…”
Section: Resultsmentioning
confidence: 99%
“…Dental pulp stem cells may thus be useful in oral and maxillofacial reconstruction (Rapino et al, 2019). During osteoblast differentiation, DPSCs express osteoblast differentiation-related biomarkers such as runt-related transcription factor 1 (RUNX1), osteocalcin (OCN), alkaline phosphatase (ALP), and osterix (OSX) (Sharpe, 2016;Victor and Reiter, 2017). Our previous studies have found that downregulation of nuclear factor erythroid 2 related factor promotes autophagy-dependent osteoblastic adipose-derived MSC differentiation (Tao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%